2010
DOI: 10.18267/j.pep.368
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Harmonisation on Distribution of VAT in the Czech Republic

Abstract: Abstract:The aim of this paper is to analyse progressivity of value added tax in the Czech Republic under the framework of both annual incidence and lifetime incidence. Moreover, impact of the harmonisation of VAT rates connected with the accession of the Czech Republic to the EU on the income distribution is examined. The burden table serves to show the distribution of the VAT burden among households by income categories; the generalised entropy measures and the Gini coeffi cient are used for measurement of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Schneider (2004) found VAT to be regressive. Klazar, Slintáková (2010) confirmed his results for annual income, but found VAT to be progressive for lifetime income. Klazar et al (2007a) is one of the most comprehensive studies of the impact of indirect taxes, whereas Klazar et al (2007b) focussed on the impact of harmonisation of VAT rates within the EU.…”
supporting
confidence: 74%
“…Schneider (2004) found VAT to be regressive. Klazar, Slintáková (2010) confirmed his results for annual income, but found VAT to be progressive for lifetime income. Klazar et al (2007a) is one of the most comprehensive studies of the impact of indirect taxes, whereas Klazar et al (2007b) focussed on the impact of harmonisation of VAT rates within the EU.…”
supporting
confidence: 74%
“…This unification or convergence will particularly affect the reduced rate of the value added tax, which would quite significantly increase under the current proposals. Slintáková and Klazar (2010) found, that the Czech VAT is regressive when the annual income is analysed, while the lifetime income analysis indicated that the VAT is progressive. Under the assumptions of fixed coefficients and inelastic demand, the VAT as well as the corporation income tax will be neutral.…”
Section: Resultsmentioning
confidence: 97%
“…A study that captures the importance of the VAT was conducted by Slintáková and Klazar (2010), who present the changes in the VAT rate encountered in the Czech Republic as a result of the harmonization process, such as a change from 23% in 1993, when this tax was introduced, to 19% in 2004, when it joined the EU.…”
Section: Introductionmentioning
confidence: 99%